MEKANISME SISTEM PROPORSIONAL TERBUKA PADA PEMILIHAN DEWAN PERWAKILAN RAKYAT DI INDONESIA - Abraham, Feri; Sudarmanto, Kukuh; Giyono, Urip (2024)
The aim of this research is to analyze the mechanism of the open proportional system in the General Election of the People's Representative Council in Indonesia by referring to Law Number 7 of 2017 concerning General Elections which regulates the open list Proportional Election System, where this system can give rise to a polemic in the struggle for seats. in a very competitive parliament that has the effect of giving birth to an unhealthy model of competition between candidates that only aims to gain as many votes as possible from voters by relying solely on money and popularity. This research method uses normative juridical in answering the problems in this paper. Meanwhile, the results of the research obtained are that an open Proportional System makes it possible for anyone to nominate themselves as members of the legislature. In this system, a person who gets the most votes can take a seat as a member of the People's Representative Council even though the person concerned is at the bottom of the ballot paper.